Description of Knowledge, Behavior, and Environment With the Incidence of Acute Respiratory Infection (ARI) in Children Under Five Years at Puskesmas Trauma Center - Shinta, Amara Wahyu Febrianshinta; Akhmad Azmiardi; Sylvia Gusrina (Panakeia Journal of Epidemiology, 2025)
Acute respiratory infections (ARI) remain one of the leading causes of illness in children under five years of age, especially in developing countries such as Indonesia. However, few studies have examined how parents' knowledge, behavior, and environmental factors together influence the occurrence of ARI. This study used a quantitative descriptive design with a cross-sectional approach, conducted at the Puskesmas Trauma Center in Samarinda from June to July 2025. Thirty-one parents of children under five years of age diagnosed with ARI were selected through accidental sampling and interviewed using a structured questionnaire. The results showed that most respondents had good knowledge about ARI prevention, but their preventive behaviors were inconsistent, such as exposure to secondhand smoke and the use of masks. Environmental risks such as household waste burning and indoor air pollution were still commonly found. These findings indicate that having good knowledge alone is not sufficient to reduce ARI cases without behavioral changes and support from the environment. This study highlights the importance of integrated public health education and environmental interventions to effectively prevent ARI in children under five years of age.